Relationship Of Antenatal Care Visits With The Incident Of Anemia In Pregnant Women In The Upt Sambau Work Area Batam City In 2024 - Rosida, Sy.; Isna Aglusi Badri, Anisya Selvia, (YUME : Journal of Management, 2024)
During pregnancy anemia can occur in pregnant women when there is a lack of iron in the blood, resulting in low hemoglobin levels. Based on data from the Batam City Health Service, the Sambau Health Center is ranked first in anemia with a total of 102 people and In fourth place, the number of pregnant women who visited was 402 people. The main objective of this research is to determine the relationship between Antenatal Care (ANC) visits and the incidence of anemia in pregnant women in the Sambau Community Health Center UPT Working Area, Batam City in 2024. This research was conducted using quantitative methods through a retrospective assessment design. Based on the results of research on the Frequency Distribution of Antenatal Care (ANC) Visits for pregnant women, it shows that of the 123 respondents, pregnant women had complete Antenatal Care (ANC) Visits, 52 pregnant women or (43.1%), pregnant women who had incomplete Antenatal Visits. Care for 71 pregnant women or (57.7%). Frequency distribution of anemia in pregnant women shows that there are 54 pregnant women who do not experience anemia or (43.9%), 69 pregnant women with anemia or (56.1%). Based on the chi-square test, a probability value (p-value) of 0.00 was obtained, which means there is a relationship between Antenatal Care Visits and the incidence of anemia in pregnant women in the Sambau Community Health Center Working Area, Batam City. Based on the results of the research above, there is a relationship between antenatal care visits and the incidence of anemia in pregnant women. Based on this, it is hoped that pregnant women can carry out routine Antenatal Care visits and Kata kunci: Antenatal Care, Anemia Pada Ibu Hamil